2019
DOI: 10.1108/tqm-01-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Testing the readiness of an organisational culture profile to a TQM implementation

Abstract: Purpose The purpose of this paper is to apply an existing theoretical model of organisational culture contextualised for total quality management (TQM) as a means of assessing the readiness for implementing TQM in the workplace. The “Amalgamated Model” is a hybrid that encapsulates organisational culture traits and their relative contribution as indictors of effective TQM implementation. Design/methodology/approach A questionnaire that would test the theoretical model was devised and administered to a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Additionally, Gurumurthy et al, (2014) in a research they conducted on organisational readiness for change to lean in manufacturing SME concluded that leadership, supplier and customer relation and employees but neglect the important role of organisational culture in their research. Moreover, organisational culture readiness to quality improvement initiatives was studied by Tenji & Foley, (2019) recently in a production facility in central Europe, the study though emphasizes on the need to assess culture prior quality improvement deployment it neglected other readiness factors that are also crucial like; process management, planning and control, customer and supplier relations.…”
Section: Research Gap On Lean Readiness Factors and Organizational Rementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Gurumurthy et al, (2014) in a research they conducted on organisational readiness for change to lean in manufacturing SME concluded that leadership, supplier and customer relation and employees but neglect the important role of organisational culture in their research. Moreover, organisational culture readiness to quality improvement initiatives was studied by Tenji & Foley, (2019) recently in a production facility in central Europe, the study though emphasizes on the need to assess culture prior quality improvement deployment it neglected other readiness factors that are also crucial like; process management, planning and control, customer and supplier relations.…”
Section: Research Gap On Lean Readiness Factors and Organizational Rementioning
confidence: 99%
“…These readiness factors include; process management, planning and control, leadership, commitment, employee involvement, supplier relation and customer relation (Al-Najem et al, 2013; Uluskan et al, 2018). Also, it is suggested further by other scholars' that such readiness factors or pre-lean conditions should be related to organisational readiness for change so as to ascertain their relationships to see whether they have not just the basic foundation, but also, the willingness and readiness to accept the change that comes with lean manufacturing deployment in their businesses (Pearce, 2019;Tenji & Foley, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1754-2731.htm (Claver et al, 2003), evolving (Zairi, 2008) and alive (Douglas, 2008). Insightful works on TQM implementation at the organizational level are increasingly emerging (G omez et al, 2017;G omez-L opez et al, 2016;Koval et al, 2018;Sila, 2020;Tenji and Foley, 2019). However, studies on TQM implementation at the individual level are hard to come by.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese Kaizen is however, different from the later and more holistic western TQM concept (Carnerud et al, 2018). TQM studies have focused on the organizational level (Shafiq et al, 2019;Tenji and Foley, 2019). Notably, aspects of the organization such as leadership (Chen et al, 2020;Kumar and Sharma, 2017), employee involvement (Haffar et al, 2019;Jurburg et al, 2017) and customer focus (Koval et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The success of TQM does not only depend on adopting the TQM attributes, but it is also dependent on complementary factors unrelated to TQM, yet more difficult to adopt than TQM itself. A corporate culture receptive to change, leadership, and motivation for improvement appear to be inevitable (Abdul, 2019;Tenji & Foley, 2019). The development quality system through applying TQM (Total Quality Management) comprises effective strategy, staff development, the introduction of instructions for product and service quality improvement and enhancing the business processes (Miterva et al, 2019).…”
mentioning
confidence: 99%